CASES OF DENTAL FLUOROSIS IN THE KEMEROVO REGION - Куприна, Ирина Владимировна; Киселева, Елена Александровна; Те, Игорь Анатольевич; Рудаева, Елена Владимировна; Мозес, Кира Борисовна; Центер, Яэль (Medicine in Kuzbass, 2023)
Concentration of the ionised fluorine in mineral water «Borisovsky» makes 7,392±0,013 mg/l and the dosed out application of mineral water «Borisovsky» can serve as an effective and cheap method of preventive maintenance of caries of a teeth in territories with the low maintenance of fluorine in potable water. Materials and methods. Among 165 children and 157 their parents for the purpose of the account of a share of participation in a drinking mode of various sources of the potable water used in families, mineral water «Borisovsky» and registration of the fact of the use by the child internal questioning was spent to milk food. We predicted probability of presence of disease. In our example group «sick patient», negative – «the healthy patient» was considered as a positive outcome. Results and discussion. As a result of our researches among schoolboys of village Borisovo high prevalence fluorosis teeth in all age groups is revealed. With reliability of 95 % it is possible to assert, that the probability of prevalence fluorosis among younger schoolboys is in the range from 43 % to 70 %; among average schoolboys - from 44 % to 67 %; among senior pupils - from 30 % to 59 %. The given logistical model is adequate and efficient as the percent of the correct classification which have turned out as a result of construction of a classification matrix, is very high (on the average 91,5 %). Conclusions. The described variant флюороза can together with wine флюорозом be carried to collective group alimentary fluorosis which needs to be entered into classification флюорозов on этиологическому to a sign. Sanitary inspection bodies should pay attention to a similar foodstuff and to take measures on prevention of their uncontrolled use. Mineral water «Borisovsky», being the reason fluorosis teeth at its excessive consumption, can serve as effective and cheap means of preventive maintenance of caries of a teeth under condition of its dispensing in territories with the low maintenance of fluorine in potable water.